Yang Menarik Bagi Masyarakat Tentang Kondisi Bangunan Kuno Di Kota Lama - Parfi Khadiyanto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2018)
This study was conducted to determine the public perception of the condition of the buildings in the old city of Semarang, what is appealing to the public. Quantitated method is used for this research, data obtained from questionnaires distributed randomly to the 100 respondents who met and are conducting activities in the Old City. The questionnaire contains ratings (based on public perception) of the elements considered most attractive, from a few choice elements of the building include building orientation, ornament, colour and facade, dimensions, architectural style, doors and windows, ceiling, walls and columns, floors, and roof. The assessment uses a Likert scale 1-5 where 1 to the lowest value (strongly disagree) and 5 for the highest value (strongly agree). The results showed that there are five components of the building are considered attractive and are of particular concern to the people; ornament; colour and façade; architectural style; doors and windows; as well as the shape of the roof of the building, it is seen that the value reached over 300, meaning that leads to agree and strongly agree as building components are interesting and deserve to be the basis of conservation.